2022
DOI: 10.1097/ta.0000000000003584
|View full text |Cite
|
Sign up to set email alerts
|

FFP maintains normal coagulation while Kcentra induces a hypercoagulable state in a porcine model of pulmonary contusion and hemorrhagic shock

Abstract: Severe injury with hemorrhagic shock induced a coagulopathy in swine. While FFP maintained normal coagulation following injury, Kcentra induced more rapid initial clot propagation in injured animals, reflective of an early hypercoagulable state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…17 PCC induced more rapid clot propagation than FFP in treating coagulopathy in pigs but resulted in lower clot strength and a higher degree of clot lysis at later time points, indicating a delayed consumptive coagulopathy. 92 Furthermore, studies have demonstrated that the ovine model of traumatic coagulopathy is essential for exploring the complex interactions between hemodynamic, metabolic, and coagulation functions in sheep. 23 Hemorrhage Combined with Femur Fractures, Liver Injury, and Hypothermia Animal models that simulate multiple traumatic injuries are useful for studying the complex interactions between injuries that can exacerbate tissue ischemia, organ dysfunction, and failure.…”
Section: Blunt Chest Injury Combined With Hemorrhage and Liver Injurymentioning
confidence: 99%
“…17 PCC induced more rapid clot propagation than FFP in treating coagulopathy in pigs but resulted in lower clot strength and a higher degree of clot lysis at later time points, indicating a delayed consumptive coagulopathy. 92 Furthermore, studies have demonstrated that the ovine model of traumatic coagulopathy is essential for exploring the complex interactions between hemodynamic, metabolic, and coagulation functions in sheep. 23 Hemorrhage Combined with Femur Fractures, Liver Injury, and Hypothermia Animal models that simulate multiple traumatic injuries are useful for studying the complex interactions between injuries that can exacerbate tissue ischemia, organ dysfunction, and failure.…”
Section: Blunt Chest Injury Combined With Hemorrhage and Liver Injurymentioning
confidence: 99%
“…Patients with TEG results meeting criteria for TIC have been shown to require more transfusions and to have higher rates of mortality 4,6 . Trauma-induced coagulopathy is also associated with higher rates of intensive care needs 8 . While both TIC has been linked to adverse clinical outcomes, there is evidence that resuscitation strategies can target these issues.…”
Section: Trauma-induced Coagulopathymentioning
confidence: 99%
“…Multiple studies, including two in our laboratory, 9,10 have found that fresh frozen plasma (FFP) reverses coagulopathy in trauma. In addition, work from our laboratory has shown that in the setting of pulmonary contusion and hemorrhagic shock in swine with coagulation abnormalities, administration of prothrombin complex concentrate (PCC) produces more rapid clot formation 8 …”
Section: Trauma-induced Coagulopathymentioning
confidence: 99%
See 2 more Smart Citations